The Influence of Transformational Leadership, Work-Life Balance, and Organizational Culture on Employee Performance in Finance Corporate - Aldi Prahasta; Muhammad Safii (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the impact of transformational leadership, work-life balance, and organizational culture on employee performance at PT Summit Oto Finance. The basis of this research is about the significance of employee performance in ensuring operational success and company competitiveness, especially in the financial services sector. The research method applied is quantitative, by collecting information using a questionnaire distributed to 100 respondents. The results of regression analysis show that transformational leadership (X1) and organizational culture (X3) have a positive and significant influence on employee performance, while work-life balance (X2) shows a significant negative influence. Assessment for validity and reliability showed that all tools utilized in the research were indeed valid and dependable. At the same time, the third independent variable significantly influences employee performance. This study highlights the significance of leadership style and organizational culture in improving performance, as well as providing more focus in the implementation of work-life balance policies.